2016
DOI: 10.1039/c6sc00817h
|View full text |Cite
|
Sign up to set email alerts
|

Well-structured bimetallic surface capable of molecular recognition for chemoselective nitroarene hydrogenation

Abstract: Unprecedented molecular recognition ability governed by a simple bimetallic surface was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 41 publications
3
87
1
Order By: Relevance
“…[2] This is acommon problem for most catalysts because they are active for the reduction of the nitro group as well as for the hydrogenation of other unsaturated functional groups (for example,C = C, C = O, and so forth) existing in the same molecule. [4] However,activation of the C = Cbond in styrene was not easy to avoid over ap rolonged reaction period, according to the results of the control experiment. [4] However,activation of the C = Cbond in styrene was not easy to avoid over ap rolonged reaction period, according to the results of the control experiment.…”
mentioning
confidence: 99%
“…[2] This is acommon problem for most catalysts because they are active for the reduction of the nitro group as well as for the hydrogenation of other unsaturated functional groups (for example,C = C, C = O, and so forth) existing in the same molecule. [4] However,activation of the C = Cbond in styrene was not easy to avoid over ap rolonged reaction period, according to the results of the control experiment. [4] However,activation of the C = Cbond in styrene was not easy to avoid over ap rolonged reaction period, according to the results of the control experiment.…”
mentioning
confidence: 99%
“…The phase diagram of the Rh–Pb system shows five room‐temperature phases (Rh 3 Pb 2 , RhPb, Rh 4 Pb 5 , RhPb 2 , RhPb 4 ) . Nanocrystalline Rh–Pb/SiO 2 catalysts (Rh 3 Pb 2 , RhPb, and RhPb 2 ) were prepared by co‐impregnation of silica templates followed by H 2 reduction . By using the microwave‐assisted polyol process RhPb 2 could be obtained (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Among others, transition metal catalyzed chemoslective reduction of nitroarenes to their respective amines has been explored using hydrazines, hydrosilanes, molecular hydrogen, sodium borohydride (NaBH 4 ), formic acid etc . Some Ru/ Pd/Pt/ Au/ Rh‐based heterogeneous catalyts have been reported for the reduction of nitroarenes. Recently, Xu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Among others, transition metal catalyzed chemoslective reduction of nitroarenes to their respective amines has been explored using hydrazines, [24][25] hydrosilanes, [26] molecular hydrogen, [27][28][29][30][31] sodium borohydride (NaBH 4 ), [32][33] formic acid [34][35] etc. Some Ru [36][37][38][39] / Pd [40][41][42][43][44][45] /Pt [46][47][48][49] / Au [50][51][52][53] / Rh [54][55][56][57] based heterogeneous catalyts have been reported for the reduction of nitroarenes. Recently, Xu et al [8] have reported reduction of nitroaromatics to aromatic amines using Pd@@g-C 3 N 4 using formic acid as source of hydrogen.…”
Section: Introductionmentioning
confidence: 99%